A Diversity of Fungal forms Present in Industrial Area of ACC Jamul - Dr Kalpana Patle , Dr. Deepak Karkun, Seema Verma , Dr. Arunima Karkun , (International Journal of Scientific Research and Management (IJSRM), 2017)
Fungi are an important microflora found in well diversified ecological conditions. In Chhattisgarh state, Jamul is situated in eastern region of Bhilai .The floral and annual diversity of Jamul is a matter of Interest. Present paper deals with the fungal diversity in Jamul. The air born fungal spores in industrial area of Jamul were studied from June 2013 to January 2014. For isolation of fungi the petriplates containing potato dextrose agar media were exposed in air and incubated at 28”C for 3 -5 days. A total of 36 fungal species were isolated. Out of which 31 species (6 genera) belongs to Deuteromycotina, 2 species (2 Genera ) belongs to Zygomycotina, 1 species ( 1 genera ) belongs to Ascomycotina and 2 sterile mycelium. Aspergillus group was found dominant followed by Penicillium and Cladosporium. It was also observed that Cladosporium species were present maximum during rainy season. The incident of fungal spores were correlated with meteorological parameters.